Political Culture of The Community in The Village Head Election in Barua, Indonesia - Julianto, Saldi; Hamrun, Hamrun; Akbar, Muhammad Randhy (Journal of Contemporary Local Politics, 2023)
This study employs community groupings based on categories of political culture to discern the political inclinations of Barua Village residents during the 2021 Pilkades in Barua Village, Eremerasa District, Bantaeng Regency. Employing descriptive research with a qualitative approach, the study methodology entails collecting observational data in the form of word lists devoid of categorization structures, followed by qualitative data analysis. Various methods, such as documentation, interviews, and observation, are utilized for qualitative data collection. Qualitative data, consisting of textually arranged words, is expanded without reliance on mathematical calculations or statistics for analysis. Through the classification of individuals based on their political cultures, this research aims to provide a comprehensive understanding of the community's political awareness and engagement levels. The study findings suggest a prevalent tendency among the Barua village community towards participant and subject political culture, evidenced by their robust political awareness, active involvement in the Pilkades process, and nuanced understanding of effective leadership. While individuals exhibit awareness of their political choices, some remain disengaged and apathetic towards political activities.